Dentists have an obligation to expand their knowlodge and to contribute to knowledge - Wood, Neil (South African Dental Journal, 2023)
Dentistry is shaped by dental research, which also drives innovation and improves oral health outcomes. As dental scientists are at the forefront of knowledge, it is important to understand their role in pushing the boundaries of research. Dentistry as a whole must promote the value of developing and funding dental research in South Africa; and draw attention to the urgent need to pay more attention to translational research. We should also emphasize the academic obligations of dental schools and faculty to advance knowledge and contribute to the literature in parallel to the provision of much needed dental services to the people of South Africa.